Effect of CFTR modulators on glucose homeostasis in children and young adults with cystic fibrosis-related diabetes: a systematic review - Giordano, Paola; Leonetti, Giuseppina; Granberg, Vanja; Casolino, Rosa Maria Pia; Lassandro, Giuseppe; Delvecchio, Maurizio; Linguiti, Giovanna (Frontiers in Endocrinology, 2025)
IntroductionCystic fibrosis (CF) is an autosomal recessive disorder caused by mutations in the CFTR gene, leading to impaired chloride transport, thickened mucus, and multiorgan dysfunction. Among its complications, cystic fibrosis-related diabetes (CFRD) is a major concern, characterized by progressive b-cell dysfunction and insulin deficiency. The advent of CFTR modulators, including ivacaftor, lumacaftor/ivacaftor, and elexacaftor/tezacaftor/ivacaftor (ETI), has revolutionized CF management by improving pulmonary function, nutritional status, and overall survival. However, their effects on glucose metabolism remain under investigation.MethodsThis systematic review (systematic review registration: PROSPERO 2025 CRD420251021499) analyzes recent evidence on the impact of CFTR modulators on CFRD in children and young adults. Results: Ivacaftor demonstrates potential benefits in glucose regulation, enhancing insulin secretion and glucagon control, particularly in patients with gating mutations. Conversely, lumacaftor/ivacaftor exhibits inconsistent effects, with some studies indicating glucose tolerance improvements while others report insulin sensitivity decline.DiscussionETI therapy shows modest but generally positive effects on glycemic control, with reductions in HbA1c and fasting glucose, though without significant changes in insulin secretion. While CFTR modulators improve systemic health, their role in directly preventing or reversing CFRD remains unclear. Further longitudinal studies are needed to optimize therapeutic strategies and elucidate the long-term metabolic effects of CFTR modulation in CF patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251021499.